THE MODEL OF BIPA LISTENING EVALUATION AND ITS IMPLICATIONS FOR THE DESIGN OF LISTENING EVALUATION - Widia, Ida; Syihabuddin, S.; Damaianti, Vismaia S.; Mulyati, Yeti (International Journal of Education, 2022)
In this paper, an analysis of the results of the evaluation of Indonesian language proficiency for foreign speakers is presented. The development of a standardized Indonesian language for foreign speakers (Bahasa Indonesia bagi Penutur Asing -  BIPA) evaluation tool is currently considered very important. Currently, the existing evaluation tools are still made partially depending on the needs of institutions that provide the Indonesian language program for foreign speakers (BIPA). In addition, this need is also driven by the need for foreign speakers to measure their proficiency in Indonesian. Although there is an Indonesian Language Proficiency Test (UKBI) as an evaluation tool in Indonesia, UKBI is considered not in accordance with the needs of measuring the Indonesian language proficiency of foreign speakers because UKBI is still used to measure the Indonesian language skills of native speakers. This has become one of the problems in the field of evaluation of the Indonesian language, especially BIPA. The language evaluation tool used to measure a person’s foreign language proficiency always begins with a listening proficiency test. Listening is considered the gateway to other language proficiency. The solution to this problem is to analyze listening evaluation tools in foreign languages that are used continuously and continuously, such as the Test of English for International Communication (TOIEC), the Japanese-Language Proficiency Test (JLPT), and Diplôme d'études en langue française (DELF), which represents three continents; American, Asian, and European spoken by Indonesian speakers. This study used a descriptive method to solve this research problem. The results of this study describe the profile of the listening proficiency evaluation tool in foreign and Indonesian languages in three ways: 1) speakers (speaker stimulus presenter), 2) content, and 3) audio. Furthermore, the results of this analysis can also be used as the basis for developing the BIPA listening competency evaluation model.